The Varieties of English Pronunciation Used by the International Visitors as Non Native English Speakers at Saung Angklung Udjo - Veralda Niantara Putri; Angkita Wasito Kirana (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2021)
This study aimed to analyzed the varieties of the English pronunciation that appeared in international visitors' speeches at Saung Angklung Udjo (SAU), Bandung. This study also analyzed how it affected the communication between the international visitors and the Guest Relation Officer (GRO) at  SAU. The data was obtained through observation, note taking and recording. We found that mostly the the different pronunciation lied on the vowel and it differed from one nationality to the other. We observed that the prununctiation is signifficantly different from the British or American English. This unfortunately caused some difficulties to understand what the visitors were speaking. The form of prununciation and the difficulties are discussed.